1979
DOI: 10.1111/j.1476-5381.1979.tb07824.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sites of Action of 5-Hydroxytryptamine in Nerve-Muscle Preparations From the Guinea-Pig Small Intestine and Colon

Abstract: 1 The sites of action of 5-hydroxytryptamine (5-HT) were examined in isolated segments of guineapig intestine. Mechanical records were taken from the longitudinal muscle of the ileum and proximal colon and from the circular muscle of the ileum and distal colon. 2 In order to examine direct actions of 5-HT, nerve-mediated responses were blocked with tetrodotoxin (0.2 jig/ml). There was a gradient in the responsiveness of the longitudinal muscle of the ileum; in the proximal ileum it was usually unresponsive, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
3
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(67 citation statements)
references
References 38 publications
11
52
3
1
Order By: Relevance
“…It was suggested that both neuronal and non-neuronal 5-HT receptors in the lon gitudinal muscle of guinea pig ileum were involved in the 5-HT-induced contraction (1)(2)(3)(4)(5)(6)(7)(8). Although the nature of the non-neuronal 5-HT receptor remains unclear, the neuronal 5-HT receptor was defined as the 5-HT3 and 5 HT4 receptor subtypes which mediated acetylcholine re lease (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that both neuronal and non-neuronal 5-HT receptors in the lon gitudinal muscle of guinea pig ileum were involved in the 5-HT-induced contraction (1)(2)(3)(4)(5)(6)(7)(8). Although the nature of the non-neuronal 5-HT receptor remains unclear, the neuronal 5-HT receptor was defined as the 5-HT3 and 5 HT4 receptor subtypes which mediated acetylcholine re lease (7).…”
Section: Resultsmentioning
confidence: 99%
“…In the gastrointestinal tract, 5-HT is reported to contribute to the regulation of the motility and secretion via several 5-HT-receptor subtypes. The in volvement of the 5-HT-receptor subtype in 5-HT-induced intestinal contraction has been well-examined in the guinea pig small and large intestines (1)(2)(3)(4)(5)(6)(7)(8). In contrast, the effect of 5-HT on the regulation of intestinal motility has not been established in species other than guinea pigs.…”
Section: -Hydroxytryptaminementioning
confidence: 99%
“…A 1.0-1.5 cm long segment of the proximal part of the hypogastric loop of the distal colon was rapidly dissected out and placed in oxygenated (96% 02 plus 4% CO2) physiological salt solution (PSS), of the following composition (mM): NaCl 119, NaHCO3 25, KCI 4.7, MgSO41.2, KH2PO4 1.2, CaCl22.5, glucose 11. The segments were suspended, in an oxygenated solution contained in a 5 ml organ bath and connected to an isometric strain gauge and a Basile 7050 recorder in such a way as to register movements ofthe longitudinal muscle, as described by Costa & Furness (1979). Bath temperature was maintained at 37°C.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…However at the higher concentration of 1.0 µM, ritanserin diminished EFS-induced contractions recorded from the rat intestine. It has been shown that the 5-HT 2 receptors are involved in mediating a contraction response to the exogenously added 5-HT, following the administration of 10 nM -0.1 µM ritanserin which could reliably block 5-HT 2 receptors in theGIT of different species (31)(32)(33). Also, in in vitro binding assays in brain tissue (34), the antagonism by ritanserin was achieved at concentrations in the nanomolar range.…”
Section: Discussionmentioning
confidence: 99%